Technology-supported dietary and lifestyle interventions in healthy pregnant women: a systematic review - O'Brien, O A; McCarthy, M; Gibney, E R; McAuliffe, F M (European journal of clinical nutrition, 2014)
Overweight and obesity are associated with increased risk of adverse maternal and fetal outcomes. However, the actuality of delivering effective lifestyle interventions in clinical practice is hampered by a high demand for resources. The use of technology to assist lifestyle interventions needs to be explored as a valid method of reducing strain on resources, and enhancing the effectiveness and population reach of interventions. The aim was to systematically review the literature on the use of technology-supported lifestyle interventions for healthy pregnant women and their impact on maternal outcomes. Online databases and registries were searched in March 2013. Primary outcomes of selected English language studies were fasting maternal glucose, incidence of gestational diabetes mellitus (GDM) and maternal gestational weight gain. Secondary outcomes were intervention uptake and acceptance, and dietary or physical activity modification. Studies whose subjects were diagnosed with GDM prior to intervention were excluded. The minimal number of eligible studies and varying outcomes precluded formal meta-analysis of the data. Initially, 203 articles were identified and screened. Seven articles, including five randomised controlled trials, met inclusion criteria for the current review. Results demonstrate several potential benefits associated with technology-supported interventions in pregnancy, despite minimal search results. Although communication technology holds potential as a safe therapeutic tool for the support of lifestyle interventions in pregnancy, there is a paucity of data on its effectiveness. Further RCTs examining the effectiveness of communication technology are required, particularly among those most likely to benefit from lifestyle interventions, such as overweight and obese pregnant women.